Response to Rituximab: Has the Original Hypothesis Been Confirmed? - Cambridge, Geraldine; De La Torre, Inmaculada (Current Pharmaceutical Design, 2015)
Before the use of rituximab, the strongest accepted evidence for an association between B-cells and rheumatoid arthritis (RA) was that clinical disease was associated with serum autoantibodies. The ability to remove B-cells with rituximab has also revealed the relative importance of the different immunological parameters that underlie the clinical symptoms of RA. First, seropositive patients have a significantly more predictable and favorable clinical response to rituximab than seronegative patients. Second, the kinetics of the clinical response, with a delay of weeks or months after depletion, suggest that it is a B-cell product (autoantibody) and not B-cells per se that need to be reduced for remission to occur. Third, removal of B-cells from joints may not be closely associated with clinical improvement, although maintenance of plasma cell counts in joints has been associated with poorer responses. The requirement of ‘new’ B-cells generated from the bone marrow for relapse to occur suggests that selection of autoreactive B-cell clones in the periphery may also be necessary for their survival and differentiation into autoantibody-producing cells. The initial hypothesis suggested that the autoimmune response underlying the pathogenesis of RA was self-sustaining. This would seem to be confirmed, as relapse inevitably follows a variable period of reduced clinical symptoms induced by rituximab. In addition, a dominant role for autoantibodies seems to have strong support from clinical practice. In addition to their possible role in the pathogenesis of RA in the form of immune complexes, further investigation is necessary to determine whether autoantibodies contribute to perpetuation of changes in central B-cell tolerance in these patients.
Keywords: Rheumatoid arthritis